2011
DOI: 10.1111/j.1552-6569.2011.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Location between Traumatic Cerebral Microbleeds and Microangiopathic Microbleeds Associated with Stroke

Abstract: There are substantial differences in locations of MB development in trauma patients in comparison to stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In our case, the clinical course suggested that a mild head injury may have caused the CMB. Traumatic CMBs tend to occur in subcortical white matter, while hypertension-related CMBs tend to occur in the basal ganglia or thalamus [2,12]. This characteristic distribution pattern is in agreement with our case.…”
Section: Discussionsupporting
confidence: 92%
“…In our case, the clinical course suggested that a mild head injury may have caused the CMB. Traumatic CMBs tend to occur in subcortical white matter, while hypertension-related CMBs tend to occur in the basal ganglia or thalamus [2,12]. This characteristic distribution pattern is in agreement with our case.…”
Section: Discussionsupporting
confidence: 92%
“…54,[68][69][70][71][72][73][74][75][76][77][78][79][80][81] CMBs are usually associated with small vessel disease such as CAA but they can also appear in a variety of other conditions including but not limited to: hemorrhagic stroke, hypertensive vasculopathy, lacunar infracts, TBI, and part of the natural aging process. They are often thought to imply an increased risk for intracranial hemorrhage and evidence is growing that the CMB lesion load is associated with cognitive decline, especially as this relates to dementia.…”
Section: Susceptibility-weighted Imaging and Quantitative Susceptibilmentioning
confidence: 99%
“…Hemorrhages in a lobar, cortico-subcortical distribution are associated with Apolipoprotein E (APOE) ε2 (35) and APOE ε4 carrier status (16, 34), β-amyloid burden on 11 C-PiB positron emission tomography (PET) (36), and evidence of CAA at post-mortem (32). In the setting of trauma, microbleeds have been reported more frequently in mid-subcortical cerebrum, above the corpus callosum, whereas non-traumatic microbleeds were found in lateral subcortical areas, basal ganglia, and thalamus (37). Microbleeds in the cerebellum have been associated with both presence of CAA and with arteriosclerotic disease (38).…”
Section: Introductionmentioning
confidence: 99%